Pengembangan Sistem Informasi Banten Menggunakan Web Semantik - Putra, I Kadek Anom Sukawirasa; Adi Paramartha, Cokorda Rai; Adi Paramartha, Cokorda Rai; Cahyadi Putra, I Gusti Ngurah Anom; Suhartana, I Ketut Gede; Widiartha, I Made; Mogi, I Komang Ari (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 2 (2022): JELIKU Volume 11 No 2, November 2022, 2022)
The culture of Bali is strongly impacted by Hindu traditions and culture, as evidenced by the numerous yadnya ceremonies that Balinese people perform. Bali is one of the Indonesian islands with a diverse range of civilizations. Banten, also known as upakara, is a strategy for aiding in the execution of a ritual in Bali. However, a current problem is that many Balinese people only have a basic understanding of this cultural legacy and are only able to recognize it. As a result, a Banten information system was created for this project, and it was based on an ontology and prototyped utilizing the prototyping approach. The Methodology technique is employed in the construction of the ontology model. The system that was created has both semantic browsing and semantic searching capabilities. Black-Box Testing was used to test the system's accuracy and operation. The system functions well as a result of the outcomes.